Radio resource and trajectory optimization for UAV assisted communication based on user route - Lei LANG; Jingning WANG; Yi WANG; Zitao ZHAO (Tongxin xuebao)
Recently, research on the application of unmanned aerial vehicle (UAV) in wireless communication networks has been widely studied.Aiming at the downlink wireless transmission system of UAV assisted mobile user communication, a method of resource allocation and trajectory optimization based on user route was proposed.According to the known user route, the estimated large-scale channel state information was obtained in advance, and a joint optimization problem of communication bandwidth allocation and trajectory optimization was established to maximize the minimum average rate of users.The problem was a nonconvex optimization problem, and there was nonlinear coupling between the variables.By introducing the method of alternating optimization of auxiliary variables and separated variables, the original problem was decomposed into two approximate convex optimization subproblems which could be solved, and the successive convex approximation was used to iteratively optimize the two subproblems, and an approximate suboptimal solution of the original nonconvex problem was obtained.Simulation results show that the proposed method of resource allocation and trajectory optimization can effectively improve the average data throughput of users, and improve the efficiency of UAV assisted communication on the premise of ensuring the communication quality of all users.